2021
DOI: 10.1021/acs.jpcb.0c11252
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Study of Isopropyl Alcohol Adsorption and Diffusion in UiO-66 Metal–Organic Framework: The Role of Missing Linker Defect

Abstract: Defect engineering leads to an effective manipulation of the physical and chemical properties of metal–organic frameworks (MOFs). Taking the common missing linker defect as an example, the defective MOF generally possesses larger pores and a greater surface area/volume ratio, both of which favor an increased amount of adsorption. When it comes to the self-diffusion of adsorbates in MOFs, however, the missing linker is a double-edged sword: the unsaturated metal sites, due to missing linkers, could interact mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 52 publications
(99 reference statements)
0
7
0
Order By: Relevance
“…[44] MOF-based OMS chemistry started with HKUST-1 (Hong Kong University of Science and Technology, BASF's Basolite C300 commodity). [205] A large body of research evidence suggests that OMS is a critical step in activating MOFs properties such as catalysis, [206][207][208][209][210] separation, [211][212][213][214] adsorption, [215][216][217][218][219] and sensing. [220,221] In this subsection, we will discuss how OMS-MOFs are a driver of photocatalytic activity.…”
Section: Defects Engineeringmentioning
confidence: 99%
“…[44] MOF-based OMS chemistry started with HKUST-1 (Hong Kong University of Science and Technology, BASF's Basolite C300 commodity). [205] A large body of research evidence suggests that OMS is a critical step in activating MOFs properties such as catalysis, [206][207][208][209][210] separation, [211][212][213][214] adsorption, [215][216][217][218][219] and sensing. [220,221] In this subsection, we will discuss how OMS-MOFs are a driver of photocatalytic activity.…”
Section: Defects Engineeringmentioning
confidence: 99%
“…Defective MOFs typically possess larger pores and a greater surface area or pore volume, leading to increased adsorption. Wang et al used computation to study the effect of missing linkers on isopropyl alcohol (IPA) adsorption and diffusion in UiO-66 . Their results showed that missing linkers and the resulting larger accessible porous volume can lead to a larger adsorption capacity of IPA but that IPA binds more strongly with uncoordinated Zr in defective regions, which results in a much slower self-diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Defects in UiO-66 introduce another dimension to its characterization and profoundly influence diffusion, , adsorption, , and catalytic properties. ,, The defects in UiO-66 are primarily of two types: missing linker defects and missing cluster defects . While the latter is harder to quantify and often detected by powder X-ray diffraction (PXRD), the former can be measured using methods like thermogravimetric analysis (TGA) and nuclear magnetic resonance (NMR), with TGA being the preferred choice for its straightforwardness. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, particle size and morphology assessments using self-assembled monolayer (SEM) and transmission electron microscopy (TEM) are generally reliable, but the specifics of the methodology can impact the results. 90 Defects in UiO-66 introduce another dimension to its characterization 91 and profoundly influence diffusion, 92,93 adsorption, 92,94−96 and catalytic properties. 65,92,97 The defects in UiO-66 are primarily of two types: missing linker defects 98 and missing cluster defects.…”
Section: Introductionmentioning
confidence: 99%